PENDIDIKAN AGAMA SEBAGAI UPAYA MENGANTISIPASI LEARNING LOSS DI SDN 023 TARAKAN - Nurul Fadilah; Siti Rahmi Rahmi; Feri Monitasari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
Islamic religious education by parents at home can be an effort of preventing learning loss to children. This is in accordance with the Circular of the Minister of Education and Culture Number 4 of 2020 which emphasizes that learning at home or distance learning is carried out to provide meaningful learning experiences for children without burdening them with demands to complete all curriculum achievements as a condition for grade promotion or graduation. The purpose of the study is to explain the efforts made in anticipating learning loss through Islamic Religious Education for children at SDN 023 Tarakan. This study uses qualitative research methods by conducting interviews to Islamic Religious Education teachers and parents of students. Education during the pandemic emphasizes more on character building and certainly with the participation of parents. However, until now there are still many parents who do not understand the essence of education during the pandemic. Therefore, effective and intensive communication is needed between teachers at school and parents at home. Through Islamic Religious Education subjects, teachers can convey what knowledge and skills to be mastered by students and what characters they want to instill in children according to their grade level. The results of the study indicate that there is a conformity between the efforts made by Islamic Religious Education teachers in implementing learning with the latest existing theory of overcoming learning loss.